Abordagem do conteúdo matemático em Modelagem Matemática na Educação Matemática: um metaestudo das produções didático pedagógicas do Programa de Desenvolvimento Educacional – PDE/PR - Loureiro, Daniel Zampieri (2016)
Considering the concern, arising from the initial teacher education, to understand how the mathematical contents have been addressed, in different methodologies and different perspectives, the argumentative text reflects the interest in illuminating the darkness of sensitizes us. Thus, we combine the theme - content approach - to Mathematical Modeling in Mathematics Education tendency. This, in turn, has gained importance in recent years, which can be verified by the diversity of events that the academic and scientific community has promoted, in addition to a variety of publications and technical works - dissertations and theses - produced under this guidance. The Interest in the trend can be justified by their dynamism, by alternatives provided through different conceptions, the reflections developed within the research group and studies that reveal ways that have not been covered. In this sense, taking into account our initial motivation and the tendency in question, it is appropriate to establish a relationship of coexistence, that is, we seek to investigate the approach of mathematical content in activities of Mathematical Modeling. Therefore, we chose to look at the activities of the Educational Development Program - PDE, understanding that research here is still incipient. Therefore, our research is based on the question "What is shows the approach of mathematical content in the didactic and pedagogical production of PDE teachers, who presented the main theme, the Mathematical Modeling?" We emphasize that the research thins to the qualitative way of proceeding, supported by a variety of procedures. The position assumed by us is the phenomenological-hermeneutics, as we seek to go-tothing- same, look at the phenomenon as it manifests itself. The way to go is illuminated from our question and this leads us to the work done by PDE teachers, more precisely the final articles. We emphasize, however, we seek those who bring in their scope the development of mathematical modeling practices, as these can be understood as a means by which we are able to access our research object - approach to mathematical content -, to this, our research takes on a metasearch character, that is, research that focuses on the research. It is worth mentioning that the developed analyzes were performed from the Atlas T.i. software which is characterized as a qualitative analysis tool. We point out that their dynamics depends "solely" the stance taken by the researcher. Taking into account the stance taken by us and the "tools" available for analysis, we seek the -epoché- reductions that culminate in large convergences - categories - which have been described and, as a result, interpreted in a metatext, seeking all what proved to be the categories in the light of our question. In this direction, it proved different aspects of the content approach to Modeling activities. These aspects say, effective approaches in the appropriation of knowledge is realized, both with respect to the teacher and the student. But they also say, innocuous approaches, even disfigured. When shown, the approach of the content comes from the PDE teacher's relationship with the supervisor, the literature used in Mathematical Modeling in Mathematics Education, the resources used to address the Mathematical content, understanding of own Mathematical Modeling and other aspects of working with content in Modeling activities.